2009
DOI: 10.1089/end.2008.0666
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Incision of Short (<3 cm) Urethral Strictures After Phallic Reconstruction

Abstract: Introduction: Urethral stricture formation is a frequent complication after phallic reconstruction, but little is known about the treatment. Endoscopic cold-knife incision has long been applied for short urethral strictures. Can this treatment be used for strictures in the phalloplasty patients as well? Materials and Methods: Thirty-two endoscopic urethrotomies were done in 22 patients with a phalloplasty. Only noncomplicated strictures shorter than 3 cm were considered appropriate for endoscopic incision. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 17 publications
0
24
2
Order By: Relevance
“…DVIU has been advocated by some in short urethral strictures as a viable option with modest success while others have reported extremely low success rate of 13% (14,15). In our practice, we have not found DVIU to be useful as a definitive strategy; its main role is as a temporizing measure to achieve urinary drainage until the patient is ready for definitive urethroplasty.…”
Section: Meatal Stenosis and Short Urethral Stricturesmentioning
confidence: 68%
“…DVIU has been advocated by some in short urethral strictures as a viable option with modest success while others have reported extremely low success rate of 13% (14,15). In our practice, we have not found DVIU to be useful as a definitive strategy; its main role is as a temporizing measure to achieve urinary drainage until the patient is ready for definitive urethroplasty.…”
Section: Meatal Stenosis and Short Urethral Stricturesmentioning
confidence: 68%
“…Urethral strictures occur more commonly in areas with poor blood flow due to ischemia such as the anastomotic sites (21,(23)(24)(25). The first-line treatment recommended for these cases is endoscopic dilation especially for short and single strictures (26). Definitive treatment is accomplished with urethroplasty through a staged procedure with buccal graft or direct repair (1).…”
Section: Review Article On Transgender Surgerymentioning
confidence: 99%
“…9 Furthermore, grafting techniques, whether using vaginal or buccal mucosa, also have a low urethral stricture rate, at 4.5% and 0%, respectively. 15,16 Much knowledge regarding urethral stricture is based on reports by Lumen et al 17,18 Their original papers indicated that the urethral anastomosis site is the most common location for stricture. Other indicated sites were the meatus, phallic urethra, fixed part urethra, and combined complex strictures, in descending order of incidence.…”
Section: Urethral Stricturementioning
confidence: 99%
“…Endoscopic incision, in the form of internal urethrotomy, was later reported as a minimally invasive alternative with similar outcomes, though its use was limited to short (less than 3 cm) stenosis. 17 They further stated that there is no reason to go beyond two incisions and that better results are to be expected if the incision is performed a long period after phalloplasty.…”
Section: Figuramentioning
confidence: 99%